Aligning ESP Courses with the Common European Framework (CEFR) for Languages - Kakoulli-Constantinou, Elis (My University, 2026)
Poster presented at the International Seminar The CEFR, the ELP and university language centres: new perspectives and new challenges, CercleS CEFR/ELP seminar